Teaching Materials Developments for Digital Native Students - Muzaki, Ferril Irham (International Journal of Scientific Research and Management (IJSRM), 2017)
The total quality management had raised the further question about changing in classroom activities. TheFurther development this idea will determine that human factors take role in total quality management,especially in developing classroom presentation. Thus, this research report is purposed to explain howclassroom management influences the students' behavior in class. Thus, the classroom presentation willmore applicable for students, also make the warm discussion, as the total quality management is used inclassroom activities. The students have to be active when they are learning in class